Non-Legal Contributions to the Concept of “Privacy”: Interdisciplinary Reflctions - Sarmiento Verbel, Adriana Romelia; Ardila Barrera, Jaime Raúl; Báez Pimiento, Adriana (DIXI, 2016)
Introduction: in order to offr a broader view of privacy, some non-legal conceptualizations are looked into, starting from the defiition established by the Diccionario de la Real Academia Española as such “intimate and reserved spiritual area of a person or group.” Methodology: the construction of the concept is consolidated throughout the article with the input of meanings from other disciplines such as psychology, philosophy and art. Results: a conceptualization that exceeds the legal framework and integrates interpretations of constitutions from other countries in the region is abstracted. Conclusion: privacy is the exercise of the radical freedom of self-determination by which humans stay true to themselves while fiding themselves inexhaustible, vast and irreducible to objects.